2010
DOI: 10.1039/c0ob00143k
|View full text |Cite
|
Sign up to set email alerts
|

Butanolysis of 4-methylbenzenediazonium ions in binary n-BuOH/H2O mixtures and in n-BuOH/SDS/H2O reverse micelles. Effects of solvent composition, acidity and temperature on the switch between heterolytic and homolytic dediazoniation mechanisms

Abstract: We investigated the effects of solvent composition, acidity and temperature on the switch between heterolytic and homolytic mechanisms in the course of the butanolysis of 4-methylbenzenediazonium (4MBD) ions in binary BuOH/H(2)O mixtures and in reverse micelles, RMs, composed of n-BuOH, H(2)O and sodium dodecyl sulfate, SDS, by employing a combination of spectrometric (UV/vis) and chromatographic (HPLC) techniques. In reaction mixtures with high n-BuOH percentages, S-shaped variations of k(obs) with acidity, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Some of their most important reactions are commonly included in organic chemistry textbooks, for example, the Sandmeyer, Gomberg–Bachman, Pschorr, Merwin, and Heck. Nevertheless, various aspects of its chemistry are still far from being completely understood . Its chemistry is dominated by the electrophilic character of the –N 2 + group, which behaves as a Lewis acid reacting with nucleophiles (Lewis bases, Nu − or NuH followed by a proton loss) to give covalently bonded adducts, ArN 2 –Nu, at β‐nitrogen of the ArN 2 + , which is the electrophilic reactive center, Scheme .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of their most important reactions are commonly included in organic chemistry textbooks, for example, the Sandmeyer, Gomberg–Bachman, Pschorr, Merwin, and Heck. Nevertheless, various aspects of its chemistry are still far from being completely understood . Its chemistry is dominated by the electrophilic character of the –N 2 + group, which behaves as a Lewis acid reacting with nucleophiles (Lewis bases, Nu − or NuH followed by a proton loss) to give covalently bonded adducts, ArN 2 –Nu, at β‐nitrogen of the ArN 2 + , which is the electrophilic reactive center, Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…Rate constants increase with the increasing pH, and a plethora of dediazoniation products, including diazo tars that are difficult to identify, are obtained, showing that mechanisms other than D N + A N or the reaction with OH − occur . In previous solvolytic work, we demonstrated that aliphatic alcohols ROH react with ArN 2 + under acidic conditions to give diazo ethers of the type E–ArN 2 OR . Formation and decomposition of such adducts were observed experimentally in the course of dediazoniations, and they are usually unstable and decompose homolytically leading to the formation of reduction products.…”
Section: Introductionmentioning
confidence: 99%